Il bilanciamento delle reazioni di ossidoriduzione: L’approccio termodinamico - Macciò, Daniele; Ottonelli, Massimo; Alloisio, Marina (Chimica nella Scuola, 2022)
The balancing of redox reactions represents one of the main difficulties encountered by students in the teaching of basic chemistry. This problem can be addressed differently depending on the academic course and the function, complementary or basic, exerted by the chemical disciplines within the course itself. This article focuses on the use of the thermodynamic method as a versatile and flexible teaching tool for balancing redox reactions in academic studies. Strengths, possible criticalities, and application methods of this approach will be discussed using redox reactions in aqueous solution.